2010
DOI: 10.1007/s13181-010-0032-7
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Conduction Disturbance Due To Prallethrin (Pyrethroid) Poisoning

Abstract: Pyrethroids are common household insecticides. Even though they are less toxic to humans, reports of accidental and suicidal poisoning are not uncommon. Cardiotoxicity due to pyrethroid poisoning is rare. We report a case of cardiac conduction disturbance due to a pyrethroid, prallethrin. A 28-year-old female presented after a suicidal consumption of prallethrin. Her clinical and laboratory parameters were normal during the first 24 h of hospital stay. On the second hospital day, she developed metabolic acidos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 7 publications
3
32
0
1
Order By: Relevance
“…The conduction system disorder caused by pyrethroids is even rarer (<1%). Bhaskar et al [8] reported a case of sinus arrest with junctional escape rhythm in a patient with an intentional overdose of prallethrin. The patient spontaneously converted to normal sinus rhythm after a few days of hospitalization with an uneventful course.…”
Section: Discussionmentioning
confidence: 99%
“…The conduction system disorder caused by pyrethroids is even rarer (<1%). Bhaskar et al [8] reported a case of sinus arrest with junctional escape rhythm in a patient with an intentional overdose of prallethrin. The patient spontaneously converted to normal sinus rhythm after a few days of hospitalization with an uneventful course.…”
Section: Discussionmentioning
confidence: 99%
“…303 Inhalation or oral ingestion of pyrethrin insecticides may lead to paresthesias, headache, nausea, vomiting, diarrhea, melena, epigastric pain, dyspnea, bronchospasm, chest pain, neural excitability, and seizures. 303,304 Cardiovascular toxicities reported with pyrethroid exposure include hypotension, sinus tachycardia, sinus arrest (with junctional escape rhythm), 304 aortic dissection, depressed left ventricular systolic function, 305 and takotsubo cardiomyopathy. 288 Pyrethroid-induced toxicity most often resolves spontaneously within 48 hours after exposure with supportive care alone.…”
Section: Pyrethroid Insecticidesmentioning
confidence: 99%
“…(1) These effects can be accompanied by the development of other undesirable effects that involve the reproductive, (2,3) immune, (4,5) cardiovascular, (6,7) respiratory (8,9) and other systems, and also contribute to a high risk of cancer development. (10) People contact pyrethroids when they are used in industrial activities and households, as well as from consumption of vegetables, fruits and water contaminated with their residues.…”
Section: Introductionmentioning
confidence: 99%